Mobilizing Alternative Modes of Cultural Governance in Berlin. - Landau, Friederike; Merkel, Janet (Palgrave Macmillan, 2019)
This chapter takes us from conceptual discussion to deep empirical engagement by investigating how urban governance is 'made' and how political actors are constituted in complex processes involving diverse actor constellations. The chapter is based on research in Berlin and revolves around the making of cultural and creative urban policy.
Keywords: Stadtforschung; Stadtplanung; Urbanität; Kreativität; Raumbezug; Kreativwirtschaft; Akteur; Kooperation; Place making Konzept; Raumkonstitution; Urban Governance; Kulturwirtschaft